POLA STRUKTUR GEOLOGI PEMBENTUK ZONA MINERALISASI DI BUKIT RANDU, KECAMATAN SELOGIRI, KABUPATEN WONOGIRI, JAWA TENGAH: GEOLOGICAL STRUCTURE PATTERNS FOR THE MINERALIZATION ZONE IN BUKIT RANDU, SELOGIRI DISTRICT, WONOGIRI REGENCY, CENTRAL JAVA - Asmoro Widagdo; Gentur Waluyo; Rachmad Setijadi; Mochammad Aziz; Huzaely Latief Sunan (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2022)
Mineralization in the Bukit Randu area and its surroundings is formed by geological structures to be investigated.This study uses data on fault striation, quartz vein plane and quartz veinlet plane. This study aims to determine the main structural pattern forming the mineralization zone. This research is useful for determining the geological structure model in the Randu Hill area. The research method was carried out through data collection in the field and analysis in the laboratory. Field data collection includes striation data measurement, quartz vein plane measurement, quartz veinlet plane and quartz vein sampling. Laboratory analysis includes stereographic analysis of striation and rose diagram analysis of vein and veinlet measurement data, and vein polishing mineragraphy. Quartz vein and veinlet mineralization in the Randu Hill area is controlled by a right lateral strike-slip fault trending northwest-southeast and a north-south normal fault. This mineralized zone is a north-south trending transtension zone due to en-enchelon right stepping of right lateral strike-slip fault. Precious metal minerals are located in the north-south trending veins in the same direction as the regional compression stress and normal faults.